2006
DOI: 10.1111/j.1574-6968.2006.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteriophages infectingSalmonellaspp.

Abstract: Bacteriophages infecting Salmonella spp. were isolated from sewage using soft agar overlays containing three Salmonella serovars and assessed with regard to their potential to control food-borne salmonellae. Two distinct phages, as defined by plaque morphology, structure and host range, were obtained from a single sample of screened sewage. Phage FGCSSa1 had the broadest host range infecting six of eight Salmonella isolates and neither of two Escherichia coli isolates. Under optimal growth conditions for S. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
117
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 19 publications
12
117
0
2
Order By: Relevance
“…This result can be explained by the possibility that a proportion of the initial bacterial population was resistant to the phage or by the rapid appearance of resistant mutants. Carey-Smith et al (11) and Fischer et al (17) proposed that the growth retardation in the presence of bacteriophage occurs when only a subpopulation of the host bacteria is susceptible to phage infection, such as the 15% of E. coli O157:H7 Mu L isolates that were resistant to phage PP01 (17). In contrast, Kocharunchitt et al (32) suggested that incomplete lysis of phage-treated bacteria was due to physiologic and/or genetic modification of host cells during phage infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result can be explained by the possibility that a proportion of the initial bacterial population was resistant to the phage or by the rapid appearance of resistant mutants. Carey-Smith et al (11) and Fischer et al (17) proposed that the growth retardation in the presence of bacteriophage occurs when only a subpopulation of the host bacteria is susceptible to phage infection, such as the 15% of E. coli O157:H7 Mu L isolates that were resistant to phage PP01 (17). In contrast, Kocharunchitt et al (32) suggested that incomplete lysis of phage-treated bacteria was due to physiologic and/or genetic modification of host cells during phage infection.…”
Section: Discussionmentioning
confidence: 99%
“…The high host specificity of most phages is a double-edged sword; high specificity is necessary for the specific targeting of unwanted bacteria, but the narrow host range renders phage biocontrol ineffective for non-host strains (22). The use of broad-hostrange phages isolated by multiple-host enrichment methods (7,11,29) or a phage cocktail composed of multiple phage types (33,44,55) has shown promise in overcoming this problem. Another limitation is the rapid emergence of phage-resistant mutants (6,11,18,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phage were precipitated from culture supernatant with 10% polyethylene glycol (6000) and 1 M sodium chloride and concentrated by centrifugation at 9,000 ϫ g for 2 h at 4°C and resuspension in phage buffer (10 mM MgSO, 10 mM Tris [pH 7.6], and 1 mM EDTA) (10,41). Phage DNA was isolated by phenol extraction, followed by ethanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Morphology of ɸSEP3 was similar to the phage FGCSSa1 [18] which had a mean head diameter of 107nm and tail length of 123 nm. The morphology of ɸSEP2 revealed greater than reported average head diameter (62.5nm) of phages belonging to family Podoviridae [19].…”
Section: Morphological Analysismentioning
confidence: 78%